CRITICAL PEDAGOGY: THE ROLE OF STUDENT DIGITAL LITERACY IN UNDERSTANDING CRITICAL PEDAGOGY - Apriyanto, Ade; Setiawardani, Wawan; Yusron, Eri (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
Technological developments encourage students to adapt and must be able to control technology with digital literacy. Critical pedagogy understanding can be the basis for students in developing pedagogy mindsets and skills. The purpose of this study is to explore how digital literacy influences students' critical pedagogy understanding. The method in this research uses an exploration method with a quantitative approach. The sample in this study is a student at one of the universities in West Java. The instrument used is a questionnaire instrument containing students' digital literacy and a test instrument containing students' critical pedagogical abilities. The instruments used have gone through expert validation. The analysis in this study uses SEM (Structural Equation Modeling) which can provide information about the effect of a variable with a complex model. The results of the analysis show that digital literacy has a significant influence on students' critical pedagogical understanding abilities. The influence is represented by the dimensions of access, evaluate and share. Although the results of the study show a positive value, there needs to be an in-depth study of how these dimensions can have an effect.